General decay and blow up of solutions for a Kirchhoff-type equation with variable-exponents - Mohammad Alnegga; Abdelbaki Choucha; Djamel Ouchenane; Salah Boulaaras (Miskolc Mathematical Notes)
A nonlinear Kirchhoff-type equation with logarithmic nonlinearity and variable exponents is studied. Firstly, the global existence is shown. Next, by using an integral inequality due to Komornik the general decay result is obtained. Finally, the blow-up of the solutions is proved.